A Study on the influence of religious beliefs on the intention to purchase sharia insurance products in Indonesia - Wijayanti, Jati; Widayanti, Catur (Edelweiss Applied Science and Technology, 2024)
This study aims to determine and explain the effect of promotion, brand awareness, and religiosity on the purchase intention of Sharia insurance, mediated by attitude. This type of research is a quantitative approach. The study used primary data with a sample of 256 respondents. The sampling technique used is purposive sampling. The data collection methode was online questionnaire. The approach used in this study is the Structural Equation Model (SEM). The result show that between the five variables – brand awareness on attitude, promotion on purchase intention, promotion on attitude, religiosity on attitude, and attitude on purchase intention have a positive and significant influence. However, religiosity not to significantly impact to purchase intention towards Sharia insurance products. Additionally, concerning mediating factors, attitude is observed to partially mediate the relationship between brand awareness and purchase intention.